Optimizing Dapodik Data Management in the Digital Era: Case Study of SMA Negeri 1 Krian - Rodiyah, Isnaini; Rustianingsih, Eni; Solicha, Fira (Indonesian Journal Publisher, 2024)
This article aims to analyze the management of Dapodik digital administration data at SMA Negeri 1 Krian. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The results showed that Dapodik data management involves planning, organizing, implementing, and controlling. However, there are several obstacles such as data discrepancies, slow servers, and system changes. Scientific findings indicate the importance of improving system efficiency and the accessibility of school operators in correcting data independently. In conclusion, optimizing Dapodik data management requires system improvements and capacity building for school operators.